Retrospective Review of Efficacy of Radiofrequency Ablation for Treatment of Colorectal Cancer Liver Metastases from a Canadian Perspective. Issue 1 (February 2014) - Kwan, Benjamin Y.M.; Kielar, Ania Z.; El-Maraghi, Robert H.; Garcia, Lourdes M.
Purpose: A retrospective single-center review of ultrasound-guided radiofrequency ablation (RFA) treatment of colorectal cancer liver metastases was performed. This study reviews the primary and secondary technical effectiveness, overall survival of patients, recurrence-free survival, tumour-free survival, rates of local recurrence, and postprocedural RFA complications. Technical effectiveness and rates of complication with respect to tumour location and size were evaluated. Our results were compared with similar studies from Europe and North America. Methods: A total of 63 patients (109 tumours) treated with RFA between February 2004 and December 2009 were reviewed. Average and median follow-up time was 19.4 and 16.5 months, respectively (range, 1–54 months). Data from patient charts, pathology, and Picture Archiving and Communication System was integrated into an Excel database. Statistical Analysis Software was used for statistical analysis. Results: Primary and secondary technical effectiveness of percutaneous and intraoperative RFA were 90.8% and 92.7%, respectively. Average (SE) tumour-free survival was 14.4 ± 1.4 months (range, 1–43 months), and average (SE) recurrence-free survival was 33.5 ± 2.3 months (range, 2–50 months). Local recurrence was seen in 31.2% of treated tumours (range, 2–50 months) (34/109). Overall survival was 89.4% at 1 year, 70.0% at 2 years, and 38.1% at 3 years, with an average (SE) overall survival of 37.0 ± 2.8 months. There were 14 postprocedural complications. There was no statistically significant difference in technical effectiveness for small tumours (1–2 cm) vs intermediate ones (3–5 cm). There was no difference in technical effectiveness for peripheral vs parenchymal tumours. Conclusions: This study demonstrated good-quality outcomes for RFA treatment of colorectal cancer liver metastases from a Canadian perspective and compared favorably with published studies.